2023
DOI: 10.1002/eng2.12667
|View full text |Cite
|
Sign up to set email alerts
|

Iron deficiency anemia detection using machine learning models: A comparative study of fingernails, palm and conjunctiva of the eye images

Abstract: Anemia is one of the global public health challenges that particularly affect children and pregnant women. A study by WHO indicates that 42% of children below the age of 6 and 40% of pregnant women worldwide are anemic. This affects the world's total population by 33%, due to the cause of iron deficiency. The non‐invasive technique, such as the use of machine learning algorithms is one of the methods used in the diagnosis or detection of clinical diseases, which anemia detection cannot be overlooked in recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…The published ML models for anemia classification all use different data than used here or perform a task other than discriminating IDA. For example, they rely on image data, or they use CBC variables to identify genetic disorders related to hemoglobin [10][11][12][13][14][15][16][17][18][19][20][27][28][29][30]. Since the cause of anemia is multifactorial [4], identifying concurrent iron deficiency is required to guide iron therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The published ML models for anemia classification all use different data than used here or perform a task other than discriminating IDA. For example, they rely on image data, or they use CBC variables to identify genetic disorders related to hemoglobin [10][11][12][13][14][15][16][17][18][19][20][27][28][29][30]. Since the cause of anemia is multifactorial [4], identifying concurrent iron deficiency is required to guide iron therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Machine learning (ML) algorithms are increasingly being used in medicine for the classification of diseases, predicting the clinical outcome [10,11]. Indeed, many studies have attempted to diagnose or classify anemia based on blood cell variables [12,13], demographic variables [14,15], images of palm [16], conjunctiva, or fingertips [17][18][19], and sickle cell anemia from images of blood smears [20], but all these studies were to diagnose anemia, rather than IDA specifically. Some studies also reported differential diagnosis of IDA and ß-thalassemia with high accuracy [12,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Anaemia happens either when the body's red blood cell production declines or the cells' structural integrity is compromised [3]. Anaemia can also appear when the haemoglobin level in the red blood cells drops below the typical threshold as a result of increases in red blood cell oxidation, blood loss, defective cells, or a reduction in the quantity of red blood cells [1].…”
Section: Introductionmentioning
confidence: 99%
“…The complexities inherent to accurately identifying the diverse causes and variations of anemia are further compounded by challenges in resource-constrained settings [ 8 ]. Although, machine learning (ML) techniques represent a promising avenue towards more efficient, accurate, and accessible detection of anemia [ 9 12 ], the integration of these technologies faces hurdles related to data quality, model generalization, and ethical considerations, necessitating a nuanced approach to harness their full potential [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, ref. [ 9 ] employed palpable palm image datasets from Ghana, utilizing a convolutional neural network (CNN) to achieve an impressive accuracy of 99.12% and F1 score of 99.89%. Another method, developed in ref.…”
Section: Introductionmentioning
confidence: 99%